Safety and tolerability of lifitegrast ophthalmic solution 5.0%: Pooled analysis of five randomized controlled trials in dry eye disease. Issue 4 (July 2019) - Nichols, Kelly K; Donnenfeld, Eric D; Karpecki, Paul M; Hovanesian, John A; Raychaudhuri, Aparna; Shojaei, Amir; Zhang, Steven
Purpose: Characterize the safety and tolerability of lifitegrast ophthalmic solution 5.0% for the treatment of dry eye disease. Methods: Pooled data from five randomized controlled trials were analyzed. Key inclusion criteria were adults with dry eye disease (Schirmer tear test score ⩾1 and ⩽10 mm, eye dryness score ⩾40 (visual analog scale 0–100), corneal staining score ⩾2.0 (0–4 scale)). Participants were randomized to lifitegrast ophthalmic solution 5.0% or placebo twice daily for 84 or 360 days. Treatment-emergent adverse events and drop comfort scores were assessed. Results: Overall, 2464 participants (lifitegrast, n = 1287; placebo, n = 1177) were included. Ocular treatment-emergent adverse events occurring in >5% in either group were instillation site irritation (lifitegrast, 15.2%; placebo, 2.8%), instillation site reaction (lifitegrast, 12.3%; placebo, 2.3%), and instillation site pain (lifitegrast, 9.8%; placebo, 2.1%); the most common (> 5%) nonocular treatment-emergent adverse event was dysgeusia (lifitegrast, 14.5%; placebo, 0.3%). The majority of treatment-emergent adverse events were mild to moderate in severity. Discontinuation due to treatment-emergent adverse events occurred in 7.0% (lifitegrast) versus 2.6% (placebo) of participants (ocular: 5.5% vs 1.5%; nonocular: 1.9% vs 1.1%). Drop comfort scores with lifitegrast improved within 3 min of instillation and the score at 3 min improved across visits (12-week trials (both eyes, day 84 vs 0): 2.0 vs 3.3; SONATA (day 360 vs 0): right eye, 1.2 vs 1.7; left eye, 1.2 vs 1.8). Conclusion: Lifitegrast ophthalmic solution 5.0% appeared to be safe and well tolerated for the treatment of dry eye disease. Drop comfort with lifitegrast improved within 3 min of instillation.